Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; image corporelle; jeunes femmes*; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Le contrôle social réservé aux femmes: entre prison, justice et travail social - Cardi, Coline (Déviance et Société, 2007)
Très peu d’études sociologiques françaises ont tenté une approche de la déviance en termes de genres: la sous-représentation statistique des femmes dans la sphère pénale suffit souvent à les écarter des analyses. Pourtant, prendre pour objet la déviance des femmes permet d’éclairer le fonctionnement du processus pénal, notamment dans son rapport avec des dispositifs parapénaux qui contribuent à distribuer de façon différentielle la déviance des hommes et celle des femmes. Ainsi, partir de la marge, que représentent les femmes incarcérées, est un moyen d’interroger le centre et de saisir en quoi, s’il faut penser la prison en lien avec l’ordre social, il faut également et conjointement la penser en lien avec l’ordre sexué et les normes qui lui sont liées.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; justice sociale; premier cycle; prison; périodes historiques; régions géographiques; sciences humaines; thématiques; travail social; trs1205; violences

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

Les clôtures symboliques des Algériennes: la virginité ou l'honneur social en question - FERHATI, Barkahoum (Clio. Femmes, Genre, Histoire, 2007)
Liée à l'honneur de la famille, la virginité est une question qui a toujours hanté l'esprit des jeunes filles algériennes. Toutes sortes de pratiques sont envisagées par la société pour la préserver. La plus connue est celles du rbat (action de nouer), dit teskar (action de fermer) ou encore tesfah (action de blinder). Au moyen de techniques ritualisées, elle consiste en la « fermeture » symbolique de l'hymen avant la puberté et son « ouverture » symbolique la veille du mariage. La « chemise tachée du sang de la vierge » doit en être la preuve indéniable: elle authentifie que l'honneur de la famille, du groupe, est intact. Lorsque, pour diverses raisons, l'hymen fait défaut, la société déploie toutes sortes de stratégies palliatives. Aujourd'hui, le certificat de virginité et la reconstitution de l'hymen par la chirurgie plastique, l'hyménorrapie ou l'hyménoplastie, viennent renforcer la pratique symbolique du rabt. La question fondamentale que je pose dans cet article est: peut-on envisager de casser la clôture « malléable » de cette « vaste prison » des femmes afin que les Algériennes puissent intégrer la société en tant qu'individus et non en tant qu'emblèmes de l'honneur de la famille?
Keywords: afrique; algérie; anthropologie; approches et analyses; corps; cours; discipline; féminisme islamique; histoire; hymen; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; rituel; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; virginité

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

‘Psy’, ‘coach’ et travail dans ‘l'entreprise du couple’: les femmes en première ligne dans Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle - Jonas, Irène (Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle, 2007)
Avec les revendications féministes, la famille a connu de nombreuses et profondes transformations au cours de ces dernières années. Elles ont pourtant été inégalement réalisées et, lorsqu’elles le furent, elles n’ont pas pour autant aplani toutes les difficultés. Ces textes traitent de l’accouchement, de l’avortement, de la contraception, du divorce, du mariage et de la recomposition familiale, des relations de couple, aux quatre coins de la francophonie: le Brésil, la France, la Grèce, le Sénégal, la Suisse et le Québec. Situations forcément différentes et pourtant questions communes susceptibles d’élargir la réflexion transfrontalière face à une institution, la famille, partout remise en cause, avec les premiers balbutiements de l’égalité des sexes. Textes de Fatou Binetou Dial, Nikoletta Chardalia, Irène Jonas, Françoise Le Borgne-Uguen, Ana Liesi Thurler, Sylvie Perrier, Éliane Perrin et son équipe, Isabelle Puech, Catherine Pugeault-Cicchelli, Lucia Scavone, Carmen Susana Tornquist, Hélène Trellu et une introduction de Marie-Blanche Tahon.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; brésil; care; corps; cours; discipline; france; francophonie; grèce; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; suisse; sénégal; thématiques; travail; travail social; trs1205

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques